Literature Review: Dysfunctional Audit Behavior - Kusumastuti, Ratih; Indayani, Indayani (JOURNAL OF ECONOMIC SCIENCE, 2015)
This paper is aimed to present a literature review about Dysfunctional Audit Behavior. It explores a recent development of this topic and offers some suggestions for future research. This paper presents a review for several findings from some journal articles and research, most of them notable accounting journals. Several sections included in this paper are the review method, topic discussion and finding of the literature review. The last section concludes the paper and suggestions for future research.